KARAKTERISTIK PETANI KAKAO DAN PRODUKSINYA DI KABUPATEN PARIGI MOUTONG - Antara, Made; Effendy, Effendy (FAPETKAN UNTAD, 2009)
ABSTRACT The research aim was to identify the characteristics of cacao farmers and factors influencing cocoa production in Parigi Moutong Regency.The research location was determined based on a Purposive method. The method to select farmers as respondents was a Simple Random Sampling. The sample size for the research was 49 respondents of 493 cocoa farmer populations. Tool analysis used to investigate factors influencing cocoa production in the research was the Cobb-Douglas production function analysis. Based on the data analysis, it can be concluded that land area, use of side grafting seedlings, fertilization, sarungisasi technology, herbicide and the farmers’ experience significantly influenced the cocoa production, whereas extension intensity had no effect on the cacao production.